Eye exenteration and facial skin defect reconstruction in a cat with Squamous Cell Carcinoma - M.S., Norfitriah; M.Y., Loqman; T.S, Gayathri; H., Hazilawati; S., Jasni; M.A., Erni Wati (Jabatan Perkhidmatan Veterinar, 2023)
Eye exenteration is one of the surgical approaches for complete excision of malignant neoplasm around the ocular region and to prevent metastasizes of cancerous cells. This paper highlights the important of surgical management of squamous cell carcinoma and skin flap technique to promote wound healing. In this case, a 10-year-old Domestic Shorthair cat with a non-healing ulcerated wound on right lower eyelid was presented to the University Veterinary Hospital (UVH), Universiti Putra Malaysia (UPM) and was diagnosed as squamous cell carcinoma (SCC) based on cytology and histopathology findings. A cluster of various abnormal squamous cells with typical characteristic of well-differentiated squamous cell carcinoma was observed under cytology examination. In addition, the ulcerated wound was rapidly increased in size and was decided for complete surgical removal of tumor in entire part of eye region. Eye exenteration followed by transpositional skin flap was applied to cover the defect area. The biopsy sample was collected and confirmed as grade 1 SCC with minimal hyperchromatism. Suction drainage was provided in the orbital spaces with application of head bandage at post-operative management to create pressure and reduce dead space. However, there are three episodes of skin flap breakdown due to presence of large dead space and seroma within the orbital space. Finally, the wound was managed as secondary intention healing until the cat was discharged.